A Pragmatic Approach to Patch Testing Atopic Dermatitis Patients: Clinical Recommendations Based on Expert Consensus Opinion. Issue 4 (July 2016) - Chen, Jennifer K.; Jacob, Sharon E.; Nedorost, Susan T.; Hanifin, Jon M.; Simpson, Eric L.; Boguniewicz, Mark; Watsky, Kalman L.; Lugo-Somolinos, Aida; Hamann, Carsten R.; Eberting, Cheryl Lee; Silverberg, Jonathan I.; Thyssen, Jacob P.
Abstract : Allergic contact dermatitis (ACD) may complicate the clinical course of atopic dermatitis (AD), and patch testing remains the criterion standard for diagnosing ACD. To date, there have been no guidelines or consensus recommendations on when and how to patch test individuals with AD. Failure to patch test when appropriate may result in overlooking an important and potentially curable complicating comorbidity. In this article, we present consensus recommendations regarding when to perform patch testing in the AD patient, best practices, and common pitfalls. Patch testing should be considered in AD patients with dermatitis that fails to improve with topical therapy; with atypical/changing distribution of dermatitis, or pattern suggestive of ACD; with therapy-resistant hand eczema in the working population; with adult- or adolescent-onset AD; and/or before initiating systemic immunosuppressants for the treatment of dermatitis. A suggested patch testing algorithm for AD patients is provided.